Strategi optimalisasi dengan metode cost struktur kini product dan SDM pada UMKM bu-dhe produksi ikan tina di kabupaten halmahera utara - Silvia, Rina; Wangka, Novriani; Meti, Yonas (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
The target of the PKM Team is the production of Tuna Bud-dhe, the problem is that partners do not understand how to determine product prices and so far, the product selling price calculations have only been based on estimates and a lack of organization of human resources. As a result, the functions and duties of employees are not optimal and have an impact on the amount of production and profits of UMKM. the solution to overcome this problem the PKM TEAM proposes appropriate technology in calculating the cost of goods sold, namely by providing knowledge of calculating the cost of goods sold with the product line cost structure and will provide knowledge and assistance in HR management so that the functions and duties of employees and owners are carried out properly. The results of the PKM activities show that after the training was carried out, the participants increased their knowledge and optimal shredded selling price.